Scare-Away Risks: The Effects of a Serious Game on Adolescents’ Awareness of Health and Security Risks in an Italian Sample - Francesca D’Errico; Paolo Giovanni Cicirelli; Concetta Papapicco; Rosa Scardigno (Multimodal Technologies and Interaction, 2022)
Digital games can be defined as games supported by audiovisual apparatus and based on storytelling. This work aims to frame video games in the recent perspective offered by positive psychology and focuses on risk perception and on the promotion of protective behaviors in adolescent students, by means of a new Italian ad hoc created digital game named ‘Scare-away risks’ (Scacciarischi). In its storytelling, the different characters must defeat monsters that symbolically represent potential risks in home, school and work contexts. On this basis, the present study assumes that playing video games, as an engaging and motivating activity, can improve the adolescents’ psychological perception of home, school and work risks. To verify these hypotheses, a quasi-experiment comparing students who played Scacciarischi (experimental group) with a control group was conducted. At the end of the game, a questionnaire was administered to 149 participants, balanced for gender, investigating (a) the level of engagement during the game, (b) the perceived risks, (c) the locus of control, (d) the protective behavior intentions. The results showed that playing Scacciarischi is related to higher levels of engagement, internal locus of control, risk perception and protective behavioral intentions. In addition, both engagement and internal locus of control act as precursors of the other two variables. Finally, reflections about the importance of the engaging experience of Scacciarischi in the domain of safety, prevention and health issues are proposed.